Organizational readiness for change: A systematic review of the healthcare literature - Laura Caci; Emanuela Nyantakyi; Kathrin Blum; Ashlesha Sonpar; Marie-Therese Schultes; Bianca Albers; Lauren Clack (Implementation Research and Practice)
Background Organizational readiness for change (ORC), referring to psychological and behavioral preparedness of organizational members for implementation, is often cited in healthcare implementation research. However, evidence about whether and under which conditions ORC is relevant for positive implementation results remains ambiguous, with past studies building on various theories and assessing ORC with different measures. To strengthen the ORC knowledge base, we therefore identified factors investigated in the empirical literature alongside ORC, or as mediators and/or moderators of ORC and implementation. Method We conducted a systematic review of experimental, observational, and hybrid studies in physical, mental, and public health care that included a quantitative assessment of ORC and at least one other factor (e.g., ORC correlate, predictor, moderator, or mediator). Studies were identified searching five online databases and bibliographies of included studies, employing dual abstract and full text screening. The study synthesis was guided by the Consolidated Framework for Implementation Research integrated with the Theory of ORC. Study quality was appraised using the Mixed Methods Appraisal Tool. Results Of 2,907 identified studies, 47 met inclusion criteria, investigating a broad range of factors alongside ORC, particularly contextual factors related to individuals and the innovation. Various ORC measures, both home-grown or theory-informed, were used, confirming a lack of conceptual clarity surrounding ORC. In most studies, ORC was measured only once. Conclusions This systematic review highlights the broad range of factors investigated in relation to ORC, suggesting that such investigation may enhance interpretation of implementation results. However, the observed diversity in ORC conceptualization and measurement supports previous calls for clearer conceptual definitions of ORC. Future efforts should integrate team-level perspectives, recognizing ORC as both an individual and team attribute. Prioritizing the use of rigorous, repeated ORC measures in longitudinal implementation research is essential for advancing the collective ORC knowledge base.